Elite wrestlers orientation to tactical information - Barna, T. (International Journal of Wrestling Science, 2013)
Movements are extremely complex in wrestling and during the match the wrestler is able to perform them thanks to his/her motor qualities. As a rule, the wrestler should possess a highly developed agility, a very rich culture of movements, and should be a fast and graceful master of many complex wrestling techniques in a variety of positions. Receiving information from the competitive environment, processing this information and selecting how to react is a basic requirement for the wrestler.